Association of Mac‐2‐binding protein glycosylation isomer level with nutritional status in chronic liver disease. Issue 9 (25th March 2018) - Eso, Yuji; Takai, Atsushi; Taura, Kojiro; Takahashi, Ken; Ueda, Yoshihide; Marusawa, Hiroyuki; Seno, Hiroshi
Abstract: Background and Aim: Mac‐2‐binding protein glycosylation isomer (M2BPGi) was recently identified as a serum glycobiomarker for liver fibrosis. However, the relationship between M2BPGi and malnutrition in patients with chronic liver disease (CLD) is unknown. We aimed to evaluate whether M2BPGi could be a surrogate marker for malnutrition in patients with CLD. Methods: In total, 338 outpatients with CLD were enrolled (median age: 67 years). We evaluated the associations among liver fibrosis markers (M2BPGi, fibrosis‐4 index, and aspartate aminotransferase‐to‐platelet count ratio index), Child–Pugh stages, and nutritional status markers. Results: The median value (range) of serum M2BPGi levels was 0.94 cut‐off index (COI) (0.22–11.57) in chronic hepatitis and Child–Pugh A ( n = 274), 4.775 COI (1.32–16.68) in Child–Pugh B ( n = 46), and 11.37 COI (6.03–18.33) in Child–Pugh C ( n = 18) (overall significance, P < 0.001). Serum M2BPGi levels showed a strong correlation with serum albumin concentration and controlling nutritional status score ( r s = −0.649, P < 0.001 and r s = 0.671, P < 0.001, respectively). The correlations between M2BPGi and nutritional status markers were especially high in patients with hepatitis C virus infection and non‐B non‐C hepatitis and patients with hepatocellular carcinoma. Among the three fibrosis markers, M2BPGi yielded the highest area under the receiver operating characteristic curve (0.920) for predicting hypoalbuminemia at an optimal cut‐off value of 2.41 (sensitivity, 87.3%; specificity, 87.6%; P < 0.001). Conclusions: Serum M2BPGi levels are correlated with nutritional status markers in patients with CLD and could be a useful clinical marker of malnutrition.